ФОРМУВАННЯ ПІЗНАВАЛЬНОГО ІНТЕРЕСУ ШКОЛЯРІВ ДО НАВЧАННЯ НА УРОКАХ З ХУДОЖНЬОЇ КУЛЬТУРИ (Педагогіка вищої та середньої школи, 2022)
In the article the concept "cognitive concern" is esteemed and its levels are investigated. The conditions of increase of a level of cognitive concern learning on lessons of the world art culture with usage of synthesis o f arts are designed.